The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5545/sv-jme.2019.6475
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Influence of Metallic Powder in Near-Dry Electric Discharge Machining

Abstract: Near-dry electrical discharge machining (ND-EDM) is an eco-friendly process. In this study, an approach has been made to make the machining process more efficient than ND-EDM with the addition of metallic powder with the dielectric medium to machine EN-31 die steel. Powdermixed near-dry EDM (PMND-EDM) has several advantages over the ND-EDM or conventional electrical discharge machining (EDM) process, such as a higher material removal rate (MRR), fine surface finish (Ra), sharp cutting edge, lesser recast laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Further increasing the concentration of powder, the WLT is slightly reduced by reducing breakdown strength and the uniform distribution of spark [53]. While increasing the graphite powder concentration in the argon gas, the lower the amount of heat energy penetrated due to the non-uniform spark concentration [20,23,54]. This leads to the formation of microcracks and pores on the machined surfaces, as shown in figures 9(a)-(c).…”
Section: Machining Mechanism Of Graphite Powder-argon Gas Assisted De...mentioning
confidence: 98%
See 1 more Smart Citation
“…Further increasing the concentration of powder, the WLT is slightly reduced by reducing breakdown strength and the uniform distribution of spark [53]. While increasing the graphite powder concentration in the argon gas, the lower the amount of heat energy penetrated due to the non-uniform spark concentration [20,23,54]. This leads to the formation of microcracks and pores on the machined surfaces, as shown in figures 9(a)-(c).…”
Section: Machining Mechanism Of Graphite Powder-argon Gas Assisted De...mentioning
confidence: 98%
“…The results of the ANOVA test indicated that nanoparticles had a favourable impact on surface polish, and the investigation′s Ra ranged from 1.88 to 4.44 μm [22]. Powder mixed near-dry EDM outperformed conventional EDM in terms of tool wear, surface roughness, material removal rate, residual stress, and micro hardness [23]. Very recently, various dry and near-dry EDM experimental research studies were performed to improve the surface and machining speed using different gases, and gas-mist dielectric fluids [24][25][26].…”
Section: Introductionmentioning
confidence: 97%
“…It was found that the material erosion rate decreased, and the electrode wear increased with an increase in reinforcing quantity in the matrix phase [15]. Some researchers [16][17][18][19] have checked the feasibility of EDM in composite materials, and their results yield that the reinforcing constituents in the matrix obstruct effective sparking and reduce matrix phase erosion.…”
Section: Introductionmentioning
confidence: 99%
“…However, the machining performance of the pure air/gas dielectric EDM process is lower than liquid processes. The airmust/ gas-mist near-dry EDM is an alternative method to enhance the performance of dry EDM (Ganachari et al 2019;Sundriyal et al 2020). Many research activities have been performed to increase the machining performance of the dry WEDM.…”
Section: Introductionmentioning
confidence: 99%